Perception of Beauty 2017
DOI: 10.5772/intechopen.69529
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation and the Perception of Beauty: Implications for an Ecological Well-Being

Abstract: Meditation is a irst-person method for contemplating ourselves and the world, with more than 2500 years of history, rooted in the philosophical and contemplative traditions of the east. The present chapter aims to explore this worldview in order to demonstrate its relevance to our capacity for the appreciation of beauty. To this end, the aesthetic experience, the contemplative experience and their relationship with the practice of mindfulness are analysed. We suggest that the contemplative meditative experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Doing so can lead an individual to insights not apparent from a superficial engagement with the art piece. Langer et al (2017) suggest that being mindful of one's aesthetic experiences enhances psychological flexibility, leading individuals to perceive the world openly. A field experiment by Zabelina et al (2020) showed that when participants engaged with art mindfully, they reported more excitement about art and recalled it better after their visit.…”
Section: Elevating the Ability To Understand Emotions With Visual Artmentioning
confidence: 99%
“…Doing so can lead an individual to insights not apparent from a superficial engagement with the art piece. Langer et al (2017) suggest that being mindful of one's aesthetic experiences enhances psychological flexibility, leading individuals to perceive the world openly. A field experiment by Zabelina et al (2020) showed that when participants engaged with art mindfully, they reported more excitement about art and recalled it better after their visit.…”
Section: Elevating the Ability To Understand Emotions With Visual Artmentioning
confidence: 99%
“…Regarding contemplative state of mind Langer et al cited that contemplative meditative experience can induce de-identification from the static self which can results with "a greater degree of psychological flexibility and a more genuine way of seeing the world, leading to a new perception of the self that is connected to an experience of freedom, and contributes to one's own well-being, as well as to that of others and of the environment. " (Langer at al. 2017).…”
mentioning
confidence: 99%